1989
DOI: 10.1902/jop.1989.60.8.429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Periodontal Dressings on Human Gingival Fibroblasts In vitro

Abstract: In vitro cytotoxicity studies of periodontal dressings have not generally produced a result consistent with in vivo observations. These prior in vitro studies have not used human intraoral cell lines. We tested the effects of two eugenol containing and two non-eugenol periodontal dressings on cultured human gingival fibroblasts (HGF) (ATCC #1292). Replicate HGF cultures grown in microtiter plates were exposed to stock, 1:4 and 1:16 dilutions of extracts made from each of the four periodontal dressings. The HGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Evaluation of the effects of periodontal dressings on gingival healing is an interesting topic of research for periodontists. Evidence shows that eugenol-containing dressings delay the process of healing [22], cause allergic reactions [11] and prevent fibroblast proliferation [7]. Several in vivo and in vitro studies [12,23-28,30] have investigated the cytotoxicity of periodontal dressings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the effects of periodontal dressings on gingival healing is an interesting topic of research for periodontists. Evidence shows that eugenol-containing dressings delay the process of healing [22], cause allergic reactions [11] and prevent fibroblast proliferation [7]. Several in vivo and in vitro studies [12,23-28,30] have investigated the cytotoxicity of periodontal dressings.…”
Section: Discussionmentioning
confidence: 99%
“…Several human and animal cell lines have been used for the assessment of the cytotoxic effects of periodontal dressings [7-9]. Eugenol-containing products can cause tissue inflammation, necrosis and allergic reactions and can subsequently delay the process of healing [10-13].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that eugenol-containing dressings showed delayed healing (Kozan and Mantell, 1978), more allergic reactions (Barkin et al, 1984) and more inhibition of fibroblast proliferation (Eber et al, 1989) compared to non-eugenol containing dressings. In the present study the cytotoxic effects of four different non-eugenol periodontal dressings and a viscous tincture on V-79 fibroblast cell culture were studied.…”
Section: Discussionmentioning
confidence: 99%
“…The use of different animal and human cell culture in vitro models for testing the cytotoxic effects of periodontal dressings may give information about biological effects in vivo (Eber et al, 1989). Several primary cell cultures and established cell lines showed different response to various periodontal dressings (Alpar et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation